Review of Francesca Vella, “Networking Operatic Italy” (2022) (Sound Stage Screen, 2023)
Review of Francesca Vella, Networking Operatic Italy (Chicago: University of Chicago Press, 2022), 256 pp., ISBN 9780226815701.